Selvmordsforebyggelse: Inddragelse af pårørende - Jensen, Jens Peter Dam Eckardt (Nordisk tidsskrift for helseforskning, 2015)
Preventing suicide: Involvement of relativesIn addition to the devastating consequences of suicide attempt and suicide contemplation, suicidal behavior also has dramatic consequences for family and loved ones. However, close connections may play an important role in the prevention of suicide if they are capable of aiding the mental health care services with early detection and management. To do so, they should be informed and given the right tools. This article sums up existing knowledge and recommendations on the topic but further studies are needed before definite conclusions can be drawn.
Keywords: pårørende; selvmord; forebyggelse; relatives; suicide; prevention